Implementation of Reading Asmaul Husna: an Effort to Increase Spiritual Intelligence - Amalia Sholekha (Jurusan Tasawuf dan Psikoterapi Fakultas Ushuluddin, Adab dan Dakwah UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
The general public tends to prioritize aspects of intellectual intelligence (IQ) over other aspects, such as spiritual intelligence (SQ). In higher education, this is reflected in the phenomenon among students who experience a lot of spiritual emptiness in studying. The education system that only teaches students in terms of academic aspects is not enough to fulfill intelligence for students. Therefore, this study aims to determine the implementation of Asmaul Husna reading in increasing the spiritual intelligence of students of the Faculty of Ushuluddin, Adab, and Da'wah (FUAD), State Islamic Institute (IAIN) Pekalongan. This type of research is field research. The method of data collection was carried out using the method of observation, interviews, filling out questionnaires, and documentation. The data that has been obtained is then analyzed using descriptive quantitative and qualitative descriptive methods. The results showed that the reading of Asmaul Husna at FUAD had a positive influence on the spiritual intelligence of students. In general, students were very enthusiastic about participating in the reading of Asmaul Husna. Research respondents who came from students obtained spiritual intelligence scores in the category range 148-246 referring to the assessment of Ary Ginanjar Agustian. The score is in the good/high category. Students implement Dhikr Asmaul Husna according to the stages in achieving the example of Dhikr Asmaul Husna, namely increasing ma’rifah through knowledge and piety; freeing oneself from the bondage of lust and lust, and purifying the soul by way of morals with the character of Allah Swt.